Elaboration of soft porous ultrasound insulators. Issue 68 (17th November 2020) - Poupart, Romain; Lacour, Thomas; Darnige, Pablo; Poncelet, Olivier; Aristégui, Christophe; Voisin, Thomas; Marre, Samuel; Brunet, Thomas; Mondain-Monval, Olivier
Abstract : A simple and easy way is proposed for the fabrication of a highly attenuating composite material for underwater acoustics. Abstract : A simple and easy way is proposed for the fabrication of a highly attenuating composite material for underwater acoustics. The approach involves the introduction of porous polymer beads into a polyurethane matrix. The porous beads are prepared through an emulsion-templating approach, and two different processes are used. The first one uses microfluidics to synthesize beads of controlled diameter and porosity. The control over the bead size allows the selection of the frequency range where the material exhibits the highest acoustic attenuation. The second one uses a double emulsion approach and allows for the production of much larger quantities of beads. Both approaches yield materials exhibiting much higher acoustic absorption than the one obtained using the most commonly used micro-balloon inclusion. We present both the synthesis procedures and the structural and acoustic characterizations of the beads and the final acoustic materials.